The role of stigmatization in developing post-traumatic symptoms after experiencing child sexual abuse by a female perpetrator. Issue 1 (1st January 2021) - Schröder, Johanna; Kratzer, Leonhard; Yamak, Yasemin; Briken, Peer; Tozdan, Safiye
ABSTRACT: Background: The context in which individuals are exposed to child sexual abuse (CSA) and reactions to the disclosure of such abuse experiences play a major role in post-traumatic mental health. Female-perpetrated CSA is an under-recognized issue in society and mental health care, and is therefore supposed to be a breeding ground for stigmatization. Objective: The aim of the current study was to examine the mediating role of internalized and anticipated stigma on the effects of so-called victim-blaming experiences and the perception of abuse in the childhood of survivors of female-perpetrated CSA on their post-traumatic symptom severity. Method: A total of 212 individuals who reported experiences of female-perpetrated CSA were assessed in an anonymous online survey. The International Trauma Questionnaire (ITQ) served as the primary outcome parameter for detecting differences in post-traumatic symptom severity within mediation analyses, where victim-blaming and abuse awareness served as predictors and anticipated as well as internalized stigma served as mediator variables. Results: Internalized stigma fully mediated the deteriorating effect of victim-blaming on post-traumatic symptom severity, while abuse awareness and anticipated stigma showed no statistically significant effects as predictor and mediator variables. Yet, victim-blaming had a significant increasing effect on anticipated stigma. Conclusions: Efforts to enhance awareness of female-perpetrated CSA in society are needed and mental health care professionals should pay attention to the adverse effects of victim-blaming and internalized stigma on post-traumatic symptoms in individuals affected by female-perpetrated CSA. HIGHLIGHTS: Child sexual abuse by women is a taboo topic. Victim-blaming by the female perpetrator is associated with post-traumatic symptoms in affected individuals. This study suggests that internalized stigma is fully accountable for this effect.